2020
DOI: 10.3390/medicina56110622
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asymmetric Dimethylarginine and Nitric Oxide with Cardiovascular Risk in Patients with End-Stage Liver Disease

Abstract: Background and objectives: Endothelial dysfunction has been proposed to be an underlying mechanism of the pronounced cardiovascular morbidity in end-stage liver disease (ESLD), but clinical evidence is still limited. In this study, we investigated the association of circulating levels of asymmetric dimethylarginine (ADMA) and nitric oxide (NO) with estimated cardiovascular risk in patients with ESLD awaiting liver transplantation. Materials and Methods: ADMA and NO levels were measured in the sera of 160 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In rats model of liver cirrhosis by bile duct ligation, Sheen JM et al [39] found that asymmetric dimethylarginine (ADMA) levels in the plasma and liver were higher in the experimental group than those in control group. Consistent with this result, plasma ADMA levels are elevated in cirrhotic patients [40] . ADMA, an analogue of Arg, is synthesized by protein methyltransferases and competes with Arg for nitric oxide synthase after proteolytic degradation.…”
Section: Discussionsupporting
confidence: 74%
“…In rats model of liver cirrhosis by bile duct ligation, Sheen JM et al [39] found that asymmetric dimethylarginine (ADMA) levels in the plasma and liver were higher in the experimental group than those in control group. Consistent with this result, plasma ADMA levels are elevated in cirrhotic patients [40] . ADMA, an analogue of Arg, is synthesized by protein methyltransferases and competes with Arg for nitric oxide synthase after proteolytic degradation.…”
Section: Discussionsupporting
confidence: 74%
“…Increased plasma nitrite/nitrate levels in individuals with decompensated cirrhosis are symptomatic of increased NO generation [15]. Cirrhosis cases and ascites had higher plasma RAAS activity and antidiuretic hormone levels, and a high serum NO level is related to reduced urine salt excretion as well as elevated plasma RAAS activity and antidiuretic hormone concentrations [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…In another study involving liver transplant candidates, asymmetric dimethylarginine (ADMA) and NO levels were classified according to the SCORE index, and it was shown that they were significantly higher in the group with high CV risk. In the study, it was emphasized that the increase in ADMA and NO levels was independently associated with the increase in CV risk [ 23 ]. The authors, who integrated the PCE CV risk scoring system with isolated post-challenge hyperglycemia in postmenopausal women, created the opportunity to perform a more sensitive risk analysis on the participants with the modified assessment system they obtained [ 24 ].…”
Section: Discussionmentioning
confidence: 99%